-43+2y+9=2(3y-2)-6

Simple and best practice solution for -43+2y+9=2(3y-2)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -43+2y+9=2(3y-2)-6 equation:


Simplifying
-43 + 2y + 9 = 2(3y + -2) + -6

Reorder the terms:
-43 + 9 + 2y = 2(3y + -2) + -6

Combine like terms: -43 + 9 = -34
-34 + 2y = 2(3y + -2) + -6

Reorder the terms:
-34 + 2y = 2(-2 + 3y) + -6
-34 + 2y = (-2 * 2 + 3y * 2) + -6
-34 + 2y = (-4 + 6y) + -6

Reorder the terms:
-34 + 2y = -4 + -6 + 6y

Combine like terms: -4 + -6 = -10
-34 + 2y = -10 + 6y

Solving
-34 + 2y = -10 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-34 + 2y + -6y = -10 + 6y + -6y

Combine like terms: 2y + -6y = -4y
-34 + -4y = -10 + 6y + -6y

Combine like terms: 6y + -6y = 0
-34 + -4y = -10 + 0
-34 + -4y = -10

Add '34' to each side of the equation.
-34 + 34 + -4y = -10 + 34

Combine like terms: -34 + 34 = 0
0 + -4y = -10 + 34
-4y = -10 + 34

Combine like terms: -10 + 34 = 24
-4y = 24

Divide each side by '-4'.
y = -6

Simplifying
y = -6

See similar equations:

| 1/2x=(x+12)1/2 | | 2.06d+18=-10.84 | | 11+(22-3^2)/4*5 | | 4(x+3)-(2s-6)= | | x-(18)=28 | | -a/8.06+7.02=18.4 | | (3(y-3))/4=-2y | | 6x^2=66x-60 | | s=9(11) | | x-(-18)=9 | | t=3n+3z | | -x-(4/5)=x+(1/2)+(2/5) | | 13/2x+4=-9 | | (16/4x-4)=(4/x) | | d=9(9) | | .59+.45t=1.74t-1.13 | | 5x-4=3y-2 | | 4n+4=-16 | | -x-(4/5)=x | | 2/3(4/5-3x)=-7/9 | | r/6=9 | | 2b+2.8=10.8+3.6b | | x^3-20x^2-64x-768=0 | | 3x-9x-13=-6x+5-13 | | -6(7v-5)=366 | | 9h=36 | | (ln(x)-1)/(ln(x))^2=0 | | 8/5+4/5x=34/15+8/3x+2/3 | | v/9=8 | | (ln(x)-1)/(ln(x))^2 | | -(5x-7y+4)= | | 30v^2-19v-63=0 |

Equations solver categories